Adverse events following immunisation with four-component meningococcal serogroup B vaccine (4CMenB): interaction with co-administration of routine infant vaccines and risk of recurrence in European randomised controlled trials. Issue 5 (19th May 2019) - Zafack, Joseline Guetsop; Bureau, Alexandre; Skowronski, Danuta M; De Serres, Gaston
Abstract : Objectives: (1) To assess if co-administration of four-component meningococcal serogroup B vaccine (4CMenB) and other routine vaccines caused an interaction increasing the risk and/or severity of adverse events following immunisation (AEFI) compared with administration at separate visits and (2) to estimate the risk of AEFI recurrence. Design: Risk-interval design Setting: Three randomised controlled trials conducted in Europe. Participants: A total of 5026 healthy 2-month-old to 15-month-old infants. Interventions: 4CMenB and routine vaccines (hexavalent combined diphtheria-tetanus-acellular pertussis-inactivated polio-Haemophilus influenzae type b-hepatitis B vaccine+seven-valent pneumococcal conjugate vaccine or measles-mumps-rubella-varicella vaccine) administered concomitantly or separately 1 month apart, in regular (2, 4, 6 and 12 months), accelerated (2, 3, 4 and 12 months) or delayed (two doses of 4CMenB at ≥12 months of age) schedules. Outcome measures: Primary: Fever (≥38°C) during the first 48 hours post immunisation. Secondary: crying, change in eating habits, diarrhoea, irritability and tenderness at the 4CMenB injection site. Results: Compared with separate administration, concomitant administration decreased the overall incidence of fever (≥38°C), 86% versus 75%, and other systemic AEFIs but increased the incidence of 4CMenB injection site tenderness, 55% versus 66%, moderate/severe fevers (≥39°C), 13% versus 18%, and long-lasting (>1 day) fevers, 23% versus 33%. Co-administration reduced AEFI risk by 4%–49% with the greatest impact among infants with prior AEFI(s). Fever recurrence risk was proportional to the number of prior fever events: 79% at dose 2 with one prior episode; 44% and 74% at dose 3 with one and two prior episodes, respectively; and 29%, 45% and 60% at dose 4 with one, two and three prior episodes, respectively. Severity was not increased at recurrence and a similar pattern of recurrence risk proportional to the number of prior events was observed for other AEFIs. Conclusions: The cumulative risk of AEFI is reduced with concomitant versus separate administration of 4CMenB and routine infant vaccines. Infants with a prior AEFI are at higher risk of the same AEFI at subsequent immunisations, but severity with recurrence is usually not increased. Trials registration number: NCT00657709, NCT00847145, NCT00721396 and NCT02712177 ; Pre-results.